(untitled) (Fiep Bulletin - online, 2014)
Despite that recent politics for teacher development in Brazil are in agreement with principles written by productive restoration and economy flexibility, the guidelines proposed by the National Education Council - NEC/2002 - enhance the strengthening of relations between development institutions and educational systems. We understand that approximating practices performed in the professor development field with Brazilian schools reality may represent an advance on teacher development and must be enhanced in initial development curriculums. We discuss in the present study, the distancing of Physical Education graduation courses from other fields in different historical moments of the Brazilian education and the possibility of approximating them starting from orientations present in the Curriculum Guidelines for teacher development. Searching in historical processes to understand aspects of the field that contributed to professional development based on apprehension of technical and instrumental knowledge, we present at the same time, the organization of the present curriculums in Physical Education, to develop teachers committed with the activity of teaching in contemporary societies.